DEVELOPING THE PHYSICAL POTENTIAL IN UNIVERSITY STUDENTS THROUGH TRAINING IN SPECIALISED SPORTS GROUPS, BASED ON THE CASE STUDY OF FITNESS AND SPORT AEROBICS (AEROBIC GYMNASTICS) - Plaksina, E.V.; Esik, Zh.V. (Theory and Practice of Physical Culture, 2022)
The study of physical and psychological profile of students at the stage of their admission to the university with a view to introducing experimental training methods in sports groups, based on the case study of fitness and sport aerobics (aerobic gymnastics). The article studies two first-year students' groups at the beginning and at the end of the academic year. The first group was trained on the standard Physical Education programme (reference group). The second, experimental group, was trained on the specialised Fitness and Sport Aerobic (Aerobic gymnastics) programme. The measurements of physical working capacity test using PWC170 test, the measurement of pulmonary capacity body mass index and the psychological anxiety level test were made. The obtained data make it possible to prove the effectiveness of physical education classes in specialised sports groups, to perfect the curriculum and raise university students' motivation for physical education, prevent the deterioration of youth health, largely related to the lack of physical activity, to reveal the physical potential of students by taking into account their individual and psychological characteristics and abilities.